GAMBARAN PENGETAHUAN IBU TENTANG PENTINGNYA BERMAIN DENGAN TEMAN SEBAYA BAGI ANAK USIA 4-6 TAHUN DI TK RIDHA KECAMATAN SUKAJADI PEKANBARU - Sari, Zelika Triana; Indarto, Wusono; Puspitasari, Enda (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Knowledge mother a deeper understanding of the importance of play with peers for children aged 4-6 years are very important because that way a mother can do more precise action against child with a view to achieving development and growth of children optimally. Play with peers for children should not be considered unimportant, because so many meanings that are found by children and especially against its development. Parents, especially mothers should be aware of the play as the childs development. With so parents should take enough time for children to socialize with peers. But the phenomenon is still assuming that play with peers it is not important. Still think that anyone can become a friend of children without limiting the childs age peers during play. Therefore, this study was conducted with the aim of describing how well the knowledge about the importance of play with peers for children aged 4-6 years in kindergarten Ridha district, Pekanbaru. The results show: 1) knowledge of mothers about the importance of play with peers for children aged 4-6 years in kindergarten Ridha district, Pekanbaru overall indicator is categorized quite well with the percentage of 51.09%. 2) From the whole, it can be seen that the indicator out higher than the other five indicators. And from these results it can be concluded that the knowledge possessed by the mother about the importance of playing with peers at the level of know who has the highest percentage of 53.07%.Keywords: Knowledge, mother, friends